PENGARUH KETERBUKAAN EKONOMI, PENDIDIKAN, DAN PENGANGGURAN TERHADAP KETIMPANGAN PENDAPATAN DI INDONESIA - Muhammad Ibnu Fatsabit; Husna Leila Yusran (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2019)
This study aim is to see the influence of economic openness, education level, and unemployment rate toward against income inequality at the provincial level in Indonesia. This study uses panel data regression analysis by using Eviews 8 analysis tools. The data used in this study is secondary data consisting of gini ratio, export/GDRB ratio, import/GDRB ratio, foreign direct investment/PDRB ratio, unemployment rate and average length of school, at 33 provinces in Indonesia in the period of 2007 to 2016. The results obtained show that only the export ratio and unemployment rate have an effect on the level of inequality in Indonesia. The export ratio has a positive and significant effect, while the unemployment rate variable has a significant negative effect.